Digital employee experience and organizational performance: a study of the telecommunications sector in Oman - Porkodi, S.; Al Balushi, Shahla Said Khamis; Al Balushi, Marwa Khalid Mohammed; Al Hadi, Khulood Othman Rashid; Al Balushi, Zulfa Is’haq Murad (Business, Management and Economics Engineering, 2023)
Purpose – The study aims at assessing the effect of digital employee experience on organisational performance, particularly in the telecommunications sector in the Sultanate of Oman, using quantitative and qualitative analysis.Research methodology – The techniques used in this empirical research include scientific literature analysis, correlation analysis, multiple regression, and sentiment analysis.Findings – The results indicate that organisational performance has a higher association with elements of the digital employee experience like work environment, organisational culture, training availability, technology accessibility, digital tool usability, and leadership support and is statistically significant at the 5% level. Also, 80% of respondents were favourable or indifferent about their digital experience.Research limitations – The study exclusively covers Oman’s telecoms industry and six important digital employee experience elements, so additional factors and industries may be examined further. A direct interview may improve findings since self-reported responses from individuals with demanding work schedules may be biased.Practical implications – Telecommunication companies must increase their efforts to engage employees in the use of digital tools and encourage their employees to utilise the different digital technologies.Originality/Value – The study investigated the six elements of the digital experience of telecom employees and its impact on organisational performance with multiple regression and sentiment analysis.